Of constituent assemblies and constitutional courts: Kashmir and the contesting of Indian sovereignty - Deva, Z (2023)
While there is significant scholarly work on the question of Kashmir in international law, constitutional law treatment of the question has remained minimal. The existing constitutional law discourse imagines the Indian union to be the sole bearer of sovereignty and therefore, Kashmir as an internal and hence, a federal question for India. My thesis project challenges this discourse by arguing that Indian sovereignty over Kashmir came to be constructed, and not inherited from the outgoing colonial state. As a consequence, it was exposed to contestations by the Kashmir government headed by Sheikh Abdullah who offered a distinct imagination of sovereignty and statehood based on the separateness of Kashmir’s constitutional order. On the other hand, Jawaharlal Nehru, independent India’ first prime minister, imagined sovereignty to be unified and absolutely vested in the Indian union, and therefore any claim to an autonomous status had to be on the terms set by the Indian constitution. I map these contestations across three negotiations on Kashmir-India constitutional relationship that take place between the two sides in between 1949 and 1952. I also show how the case of Kashmir speaks to the other traditions where constitutional authority has come to be shared between two entities. From the two governments and the constituent assemblies, I shift my focus to the constitutional courts in Kashmir and India, and how they imagine Kashmir’s status in the early 1950s. I argue that both of the constitutional courts are more receptive to the claims of constitutional pluralism than the other central institutions and actors. I situate the Kashmir cases in the federal jurisprudence of the Indian constitutional court in its early years, as well as the wider socio-political context in which these cases were decided.